Liver transplantation for unresectable colorectal liver metastasis: Who will get the benefit?. Issue 2 (28th December 2019) - Goto, Toru; Selzner, Markus
Abstract : Patients with unresectable colorectal liver metastasis should be assessed for appropriate treatment protocols, which should include the option for liver transplantation. Dueland et al's article is on page 530 .